HUBUNGAN SELF EFFICACY DENGAN MANAJEMEN DIRI PASIEN HIPERTENSI DI RUMAH SAKIT UMUM SEMBIRING - rentawati (Jurnal Penelitian Keperawatan Medik, 2026)
Hypertension is a dangerous non-communicable disease prevalent worldwide. In 2019, the global prevalence of hypertension reached 22% of the world's population, while in Indonesia, the prevalence stood at 34.11%. Hypertension requires long-term disease management by the patient. Self-management is closely related to patient behavior, and one of the factors influencing self-management is self-efficacy. This study aimed to determine the relationship between self-efficacy and self-management among hypertensive patients. This study was quantitative study utilizing a cross-sectional design. The sample consisted of 54 respondents identified through blood pressure measurements, with data collected via structured questionnaires. Bivariate analysis was conducted using the Chi-Square statistical test with a significance level of p < 0.05. Based on respondent characteristics at Sembiring General Hospital Deli Tua. The sample was dominated by females (25 respondents, 46.3%) and individuals aged over 50 years (31 respondents, 57.4%). The most common occupation was entrepreneurship (19 respondents, 35.2%). The results of the study indicated that a significant relationship between self-efficacy and self-management in hypertensive patients. It is expected that patients will improve their self-management by regularly monitoring their blood pressure, low salt diet, sugar and fat, doing physical activity, regular rest pattern adhering to antihypertensive medication, and adopting a healthy lifestyle.